Wavelength conversion component and light emitting device using the same
By reducing alkali metal components and increasing alkaline earth oxides in the glass matrix, the formation of coloring centers is suppressed, and the problem of reducing the luminous intensity of wavelength conversion components over time is solved, the long-term reliability of the light emitting device is improved, and it is suitable for applications such as on-board lighting.
Patent Information
- Application Number
- CN202210789175.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-06-27
- Filing Date
- 2017-06-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2037-06-08
AI Technical Summary
When the existing wavelength conversion components use LED or LD light sources, the light emission intensity decreases over time, especially in the case of high output power, which leads to a decrease in reliability of the light emitting device under long-term use.
By dispersing the wavelength conversion member with inorganic phosphors in the glass matrix, the alkali metal component in the glass matrix is reduced, the formation of a coloring center is suppressed, and the softening point of the glass matrix is reduced by using alkaline earth oxides to reduce the deterioration of inorganic phosphors during production.
It effectively reduces the time reduction of luminous intensity, improves the long-term reliability of light emitting devices, and is suitable for applications such as on-board lighting and headlights.
Smart Images

Figure CN115172566B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a wavelength conversion component for converting the wavelength of light emitted by a light emitting element such as a light emitting diode (LED) or a laser diode (LD) into another wavelength. Background Art
[0002] In recent years, as a next-generation light source to replace fluorescent lamps or incandescent lamps, light sources using LEDs and LDs have attracted increasing attention from the perspectives of low power consumption, small size, light weight, and easy light quantity adjustment. As an example of such a next-generation light source, for example, Patent Document 1 discloses a light source in which a wavelength conversion component that absorbs a portion of the light from the LED and converts it into yellow light is arranged on an LED that emits blue light. The light source emits white light that is a composite of the blue light emitted from the LED and the yellow light emitted from the wavelength conversion component.
[0003] As wavelength conversion components, components in which inorganic phosphors are dispersed in a resin matrix have been used. However, when using such wavelength conversion components, there is a problem that the resin is degraded by the light from the LED and the brightness of the light source is easily reduced. In particular, there is a problem that the resin matrix is degraded, discolored, and deformed by the heat or high-energy short-wavelength (blue to ultraviolet) light emitted by the LED.
[0004] Therefore, a wavelength conversion component composed of a completely inorganic solid in which an inorganic phosphor is dispersed and fixed in a glass matrix instead of a resin has been proposed (for example, see Patent Documents 2 and 3). The wavelength conversion component has the following characteristics, that is, the glass serving as the base material is not easily degraded by the heat or irradiation light of the LED chip, and is not easily discolored or deformed.
[0005] However, the wavelength conversion components described in Patent Documents 2 and 3 have the problem that the inorganic phosphor deteriorates and the brightness is easily deteriorated due to the firing during manufacturing. In particular, in the use of general lighting, special lighting, etc., high color rendering is required, so it is necessary to use inorganic phosphors with relatively low heat resistance such as red and green, and there is a tendency for the inorganic phosphor to deteriorate significantly. Therefore, a wavelength conversion component containing alkali metal oxides in the glass composition to reduce the softening point of the glass powder is proposed (for example, refer to Patent Document 4). This wavelength conversion component can be manufactured by firing at a relatively low temperature, so it is possible to suppress the degradation of the inorganic phosphor during firing.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2000-208815
[0009] Patent Document 2: Japanese Patent Application Publication No. 2003-258308
[0010] Patent Document 3: Japanese Patent No. 4895541
[0011] Patent Document 4: Japanese Patent Application Publication No. 2007-302858 Summary of the invention
[0012] Problems to be solved by the invention
[0013] The wavelength conversion member described in Patent Document 4 has a problem that the emission intensity is easily reduced over time (temperature extinction). With the further increase in the output power of light sources such as LEDs and LDs in recent years, the reduction in emission intensity over time has become more significant.
[0014] In view of the above circumstances, an object of the present invention is to provide a wavelength conversion member having less decrease in emission intensity over time when irradiated with light from LED or LD, and a light emitting device using the wavelength conversion member.
[0015] Methods for solving problems
[0016] The wavelength conversion component of the present invention is characterized in that it is a wavelength conversion component in which an inorganic phosphor is dispersed in a glass matrix, and the glass matrix contains, in mole %, 30 to 85% SiO2, 0 to 20% B2O3, 0 to 25% Al2O3, 0 to 3% Li2O, 0 to 3% Na2O, 0 to 3% K2O, 0 to 3% Li2O+Na2O+K2O, 0 to 35% MgO, 0 to 35% CaO, 0 to 35% SrO, 0 to 35% BaO, 0.1 to 45% MgO+CaO+SrO+BaO, and 0 to 4% ZnO, and the inorganic phosphor is at least one selected from oxide phosphors, nitride phosphors, oxynitride phosphors, chloride phosphors, acyl chloride phosphors, halide phosphors, aluminate phosphors and halophosphate phosphors. Here, “○+○+···” means the total amount of each component.
[0017] The inventors of the present invention have found that the cause of the decrease in the luminous intensity of the wavelength conversion member over time is particularly due to the alkali metal components contained in the glass composition. The mechanism is presumed to be as follows.
[0018] It can be considered that if the glass matrix containing alkali metal elements in the composition is irradiated with excitation light, the outermost electrons of the oxygen ions present in the glass matrix are excited due to the energy of the excitation light and detached from the oxygen ions. A part of them combines with the alkali metal ions in the glass matrix to form a coloring center (wherein, a hole is formed after the alkali metal ions are detached). On the other hand, since the holes generated by the detachment of the electrons move in the glass matrix, a part of them is captured by the holes formed after the alkali metal ions are detached to form a coloring center. These coloring centers formed in the glass matrix become absorption sources of excitation light and fluorescence, reducing the luminous intensity of the wavelength conversion component. Furthermore, due to the heat generated by the inorganic phosphor (heat generated due to wavelength conversion loss), there is a tendency for the movement of electrons, holes, and alkali metal ions in the glass matrix to become active. As a result, the formation of coloring centers is accelerated and the luminous intensity is easily reduced.
[0019] In the wavelength conversion component of the present invention, the generation of coloring centers is suppressed by minimizing the content of alkali metal components in the glass matrix as described above. In addition, by minimizing the content of alkali metal components in the glass matrix, it is also possible to suppress the glass matrix from deteriorating over time under high temperature and high humidity.
[0020] In addition, the glass matrix in the wavelength conversion component of the present invention contains alkaline earth oxides (MgO, CaO, SrO, BaO) as essential components. Alkaline earth oxides do not affect the time-dependent decrease in the luminous intensity of the wavelength conversion component like alkali metal ions, and can also reduce the softening point of the glass matrix. Thus, it is possible to suppress the degradation of the characteristics of the inorganic phosphor caused by firing during manufacturing.
[0021] In the wavelength conversion component of the present invention, the glass matrix preferably contains, in mol%, 30 to 85% SiO2, 0 to 20% B2O3, 0 to 25% Al2O3, 0 to 3% Li2O, 0 to 3% Na2O, 0 to 3% K2O, 0 to 3% Li2O+Na2O+K2O, 0 to 35% MgO, 0 to 35% CaO, 0 to 35% SrO, 0 to 35% BaO, 0.1 to 45% MgO+CaO+SrO+BaO and more than 0 and less than 1.8% ZnO.
[0022] In the wavelength conversion member of the present invention, it is preferred that the softening point of the glass matrix is 600 to 1100°C.
[0023] The wavelength conversion member of the present invention preferably contains 0.01 to 70% by mass of an inorganic phosphor.
[0024] The wavelength conversion member of the present invention is preferably formed of a powder sintered body.
[0025] The light emitting device of the present invention is characterized by comprising the above-mentioned wavelength conversion member and a light source for irradiating the wavelength conversion member with excitation light.
[0026] The vehicle-mounted lighting of the present invention is characterized by using the above-mentioned light-emitting device.
[0027] The vehicle-mounted lighting device of the present invention is characterized in that it is used as a headlamp.
[0028] Effects of the Invention
[0029] The wavelength conversion component of the present invention has little decrease in luminous intensity over time when irradiated with light from an LED or LD. Therefore, the light-emitting device using the wavelength conversion component of the present invention has excellent long-term reliability and is suitable for vehicle-mounted lighting, particularly for vehicle-mounted headlights. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a schematic side view of a light emitting device according to one embodiment of the present invention. DETAILED DESCRIPTION
[0031] The wavelength conversion component of the present invention is formed by dispersing an inorganic phosphor in a glass matrix. The glass matrix contains, in terms of mole %, 30 to 85% SiO2, 0 to 20% B2O3, 0 to 25% Al2O3, 0 to 3% Li2O, 0 to 3% Na2O, 0 to 3% K2O, 0 to 3% Li2O+Na2O+K2O, 0 to 35% MgO, 0 to 35% CaO, 0 to 35% SrO, 0 to 35% BaO, 0.1 to 45% MgO+CaO+SrO+BaO, and 0 to 4% ZnO. The reason for limiting the glass composition range in this way is described below. In addition, in the following description, "%" means "mole %" unless otherwise specified.
[0032] SiO2 is a component that forms a glass network. The content of SiO2 is 30 to 85%, preferably 35 to 80%. If the content of SiO2 is too low, there is a tendency for weather resistance and mechanical strength to decrease. On the other hand, if the content of SiO2 is too high, the sintering temperature becomes high, so when manufacturing a wavelength conversion component, the inorganic phosphor is easily degraded.
[0033] B2O3 is a component that lowers the melting temperature and significantly improves the solubility. The content of B2O3 is 0 to 20%, preferably 0.1 to 18%. If the content of B2O3 is too high, the weather resistance is likely to decrease.
[0034] Al2O3 is a component that improves weather resistance and mechanical strength. The content of Al2O3 is 0 to 25%, preferably 0.1 to 20%. If the content of Al2O3 is too high, the meltability tends to decrease.
[0035] Li2O, Na2O and K2O are components that lower the melting temperature and improve the solubility while lowering the softening point. However, if the content of these components is too much, the weather resistance is easily reduced, and the luminous intensity is easily reduced over time due to the light irradiation of LED and LD. Therefore, the content of Li2O+Na2O+K2O is 0-3%, preferably 0-2%. In addition, the content of each component of Li2O, Na2O and K2O is 0-3%, preferably 0-2%. In the case of containing Li2O, Na2O, and K2O, it is preferably mixed and used in combination of two or more, and it is particularly preferred to mix and use three. If set in this way, the reduction in luminous intensity over time caused by the light irradiation of LED and LD can be suppressed through the effect of the mixed alkali.
[0036] MgO, CaO, SrO and BaO are components that lower the melting temperature and improve the solubility while lowering the softening point. In addition, as mentioned above, these components, unlike the alkali metal components, do not affect the time-dependent decrease in the luminous intensity of the wavelength conversion component. The content of MgO+CaO+SrO+BaO is 0.1-45%, preferably 0.1-40%, 0.1-35%, 1-30%, and particularly preferably 5-25%. If the content of MgO+CaO+SrO+BaO is too little, it is difficult to lower the softening point. On the other hand, if the content of MgO+CaO+SrO+BaO is too much, the weather resistance is easily reduced. In addition, the content of each component of MgO, CaO, SrO and BaO is preferably 0-35%, 0.1-33%, and particularly preferably 1-30%, respectively. If the content of these components is too much, there is a tendency for the weather resistance to decrease.
[0037] ZnO is a component that lowers the melting temperature and improves solubility. The content of ZnO is 0 to 4%, preferably 0 to 3%, more preferably 0 or more and less than 1.8%, and even more preferably 0.1 to 1.5%. If the content of ZnO is too much, there is a tendency for weather resistance to decrease. In addition, phase separation occurs and transmittance decreases, resulting in a tendency for luminous intensity to decrease.
[0038] In addition to the above-mentioned components, various components may be contained within a range that does not impair the effects of the present invention. For example, P2O5, La2O3, Ta2O5, TeO2, TiO2, Nb2O5, Gd2O3, Y2O3, CeO2, Sb2O3, SnO2, Bi2O3, As2O3, and ZrO2 may be contained in an amount of less than 15%, more preferably less than 10%, and in an amount of less than 5%, and in an amount of less than 30% in total. In addition, F may be contained. Since F has the effect of lowering the softening point, by containing F instead of the alkali metal component that is one of the causes of the formation of the coloring center, it is possible to suppress the decrease in luminous intensity over time while maintaining a low softening point. The content of F is preferably 0 to 10%, 0 to 8%, and particularly preferably 0.1 to 5% in terms of anion %.
[0039] Fe and Cr are components that reduce the visible light transmittance and become the cause of reduced luminous intensity. Therefore, the Fe content is preferably less than 1000ppm, and particularly preferably less than 500ppm. In addition, the Cr content is preferably less than 500ppm, and particularly preferably less than 100ppm. Among them, in order to make the glass free of Fe and Cr, it is necessary to use expensive high-purity raw materials, so the manufacturing cost is prone to increase. Therefore, from the viewpoint of reducing manufacturing costs, the Fe and Cr contents are preferably more than 5ppm, and particularly preferably more than 10ppm.
[0040] The softening point of the glass matrix is preferably 600 to 1100° C., 630 to 1050° C., and particularly preferably 650 to 1000° C. If the softening point of the glass matrix is too low, the mechanical strength and weather resistance are likely to decrease. On the other hand, if the softening point is too high, the sintering temperature also becomes high, so the inorganic phosphor is likely to deteriorate during the firing process during manufacturing.
[0041] The inorganic phosphor of the present invention is at least one selected from oxide phosphors (including garnet-based phosphors such as YAG phosphors), nitride phosphors, oxynitride phosphors, chloride phosphors, acyl chloride phosphors, halide phosphors, aluminate phosphors, and halophosphate phosphors. Among these inorganic phosphors, oxide phosphors, nitride phosphors, and oxynitride phosphors have high heat resistance and are less likely to deteriorate during firing, so they are preferred. In addition, nitride phosphors and oxynitride phosphors convert near-ultraviolet to blue excitation light into a wide range of green to red wavelengths, and have the characteristic of relatively high luminous intensity. Therefore, nitride phosphors and oxynitride phosphors are particularly effective as inorganic phosphors for wavelength conversion components for white LED elements. In order to suppress the conduction of heat generated by the inorganic phosphor to the glass matrix, a coated inorganic phosphor can also be used. As a result, the activation of the movement of electrons, holes, and alkali metal ions in the glass matrix can be suppressed, and as a result, the formation of coloring centers can be suppressed. As the coating material, oxides are preferred. In addition, as phosphors other than the above, sulfide phosphors can be cited, but sulfide phosphors are not used in the present invention because they deteriorate over time or react with the glass matrix to easily reduce the emission intensity.
[0042] As the above-mentioned inorganic phosphors, there can be listed phosphors having an excitation band at a wavelength of 300 to 500 nm and a luminescence peak at a wavelength of 380 to 780 nm, in particular phosphors emitting blue (wavelength 440 to 480 nm), green (wavelength 500 to 540 nm), yellow (wavelength 540 to 595 nm), and red (wavelength 600 to 700 nm).
[0043] Examples of inorganic phosphors that emit blue light when irradiated with ultraviolet to near-ultraviolet excitation light having a wavelength of 300 to 440 nm include (Sr, Ba)MgAl 10 O 17 :Eu 2+ 、(Sr,Ba)3MgSi2O8:Eu 2+ wait.
[0044] Examples of inorganic phosphors that emit green fluorescence when irradiated with ultraviolet to near-ultraviolet excitation light with a wavelength of 300 to 440 nm include SrAl2O4:Eu 2+ 、SrBaSiO4:Eu 2+ 、Y3(Al,Gd)5O 12 :Ce 3+ 、SrSiON:Eu 2+ 、BaMgAl 10 O 17 :Eu 2+ , Mn 2+ 、Ba2MgSi2O7:Eu2+ 、Ba2SiO4:Eu 2+ 、Ba2Li2Si2O7:Eu 2+ 、BaAl2O4:Eu 2+ wait.
[0045] Examples of inorganic phosphors that emit green fluorescence when irradiated with blue excitation light having a wavelength of 440 to 480 nm include SrAl2O4:Eu 2+ 、SrBaSiO4:Eu 2+ 、Y3(Al,Gd)5O 12 :Ce 3+ 、SrSiON:Eu 2+ 、β-SiAlON:Eu 2+ wait.
[0046] Examples of inorganic phosphors that emit yellow fluorescence when irradiated with ultraviolet to near-ultraviolet excitation light having a wavelength of 300 to 440 nm include La3Si6N 11 :Ce 3+ wait.
[0047] Examples of inorganic phosphors that emit yellow fluorescence when irradiated with blue excitation light having a wavelength of 440 to 480 nm include Y3(Al,Gd)5O 12 :Ce 3+ 、Sr2SiO4:Eu 2+ .
[0048] Examples of inorganic phosphors that emit red fluorescence when irradiated with ultraviolet to near-ultraviolet excitation light with a wavelength of 300 to 440 nm include MgSr3Si2O8:Eu 2+ , Mn 2+ 、Ca2MgSi2O7:Eu 2+ , Mn 2+ wait.
[0049] Examples of inorganic phosphors that emit red fluorescence when irradiated with blue excitation light having a wavelength of 440 to 480 nm include CaAlSiN3:Eu 2+ 、CaSiN3:Eu 2+ 、(Ca,Sr)2Si5N8:Eu 2+ 、α-SiAlON:Eu 2+ wait.
[0050] In addition, a plurality of inorganic phosphors may be mixed and used according to the wavelength range of the excitation light and the luminescence. For example, when white light is to be obtained by irradiating ultraviolet excitation light, inorganic phosphors emitting blue, green, yellow, and red fluorescence may be mixed and used.
[0051] In addition, generally speaking, in most cases, the refractive index of inorganic phosphors is higher than that of glass. In the wavelength conversion component, if the refractive index difference between the inorganic phosphor and the glass matrix is large, the excitation light is easily scattered at the interface between the inorganic phosphor and the glass matrix. As a result, the irradiation efficiency of the excitation light relative to the inorganic phosphor is improved, and the luminous efficiency is easily increased. However, if the refractive index difference between the inorganic phosphor and the glass matrix is too large, the scattering of the excitation light becomes excessive, which becomes a scattering loss, and there is a tendency for the luminous efficiency to decrease. In view of the above, the refractive index difference between the inorganic phosphor and the glass matrix is preferably about 0.001 to 0.5. In addition, the refractive index (nd) of the glass matrix is preferably 1.45 to 1.8, more preferably 1.47 to 1.75, and even more preferably 1.48 to 1.6.
[0052] The luminous efficiency (lm / W) of the wavelength conversion component varies depending on the type and content of the inorganic phosphor, and the thickness of the wavelength conversion component. The content of the inorganic phosphor and the thickness of the wavelength conversion component can be appropriately adjusted in such a way that the luminous efficiency is optimized. If the content of the inorganic phosphor is too much, it may be difficult to sinter, the porosity becomes larger and the excitation light is difficult to efficiently irradiate the inorganic phosphor, and the mechanical strength of the wavelength conversion component is reduced. On the other hand, if the content of the inorganic phosphor is too little, it is difficult to obtain the desired luminous intensity. From this point of view, the content of the inorganic phosphor in the wavelength conversion component of the present invention is preferably 0.01 to 70% by mass, more preferably 0.05 to 50% by mass, and even more preferably 0.08 to 30% by mass.
[0053] In addition, in a wavelength conversion component whose purpose is to reflect the fluorescence generated in the wavelength conversion component toward the incident side of the excitation light and mainly to extract only the fluorescence to the outside, it is not limited to the above content, and the content of inorganic phosphor can be increased in a manner to maximize the luminous intensity (for example, 30 to 80 mass %, and further 40 to 75 mass %).
[0054] The wavelength conversion member of the present invention may contain up to 30% by mass in total of a light diffusing material such as aluminum oxide, silicon oxide, or magnesium oxide in addition to the inorganic phosphor.
[0055] The wavelength conversion component of the present invention is preferably formed of a powder sintered body. Specifically, it is preferably formed of a sintered body of a mixed powder containing glass powder and inorganic phosphor powder. In this way, it is easy to produce a wavelength conversion component in which the inorganic phosphor is uniformly dispersed in the glass matrix.
[0056] The maximum particle size of glass powder D max The average particle size D of the glass powder is preferably 200 μm or less, 150 μm or less, and particularly preferably 105 μm or less. 50It is preferably 0.1 μm or more, 1 μm or more, and particularly preferably 2 μm or more. max If the average particle size D of the glass powder is too large, the excitation light is difficult to scatter in the obtained wavelength conversion component, and the luminous efficiency is likely to decrease. 50 If it is too small, the excitation light is excessively scattered in the obtained wavelength conversion member, and the light emission efficiency is likely to decrease.
[0057] In addition, in the present invention, the maximum particle size D max and average particle size D 50 It refers to the value measured by laser diffraction method.
[0058] The firing temperature of the mixed powder containing glass powder and inorganic phosphor is preferably within ±150°C of the softening point of the glass powder, and particularly preferably within ±100°C of the softening point of the glass powder. If the firing temperature is too low, the glass powder cannot flow sufficiently, and it is difficult to obtain a dense sintered body. On the other hand, if the firing temperature is too high, the inorganic phosphor component may dissolve in the glass and the luminous intensity may decrease, or the inorganic phosphor component may diffuse in the glass, causing the glass to be colored and the luminous intensity to decrease.
[0059] The firing is preferably carried out in a reduced pressure atmosphere. Specifically, the atmosphere during firing is preferably less than 1.013×10 5 Pa, 1000Pa or less, and particularly preferably 400Pa or less. Thus, the amount of bubbles remaining in the wavelength conversion component can be reduced. As a result, the scattering factor in the wavelength conversion component can be reduced, and the luminous efficiency can be improved. In addition, the entire firing process can be performed in a reduced pressure atmosphere, or only the firing process can be performed in a reduced pressure atmosphere, and the heating process and the cooling process before and after are performed in a non-reduced pressure atmosphere (e.g., under atmospheric pressure).
[0060] The shape of the wavelength conversion component of the present invention is not particularly limited. For example, it can be not only a component having a specific shape such as a sheet, column, hemispherical, hemispherical dome, etc., but also a sintered body in the form of a coating formed on the surface of a substrate such as a glass substrate or a ceramic substrate.
[0061] In addition, an anti-reflection film or a fine concavo-convex structure layer may be provided on the surface of the wavelength conversion member. By providing such an anti-reflection film or a fine concavo-convex structure layer, the light reflectivity of the surface of the wavelength conversion member is reduced, the light extraction efficiency is improved, and the luminous intensity can be increased.
[0062] As the anti-reflection film, a single layer film or a multilayer film (dielectric multilayer film) containing oxides, nitrides, fluorides, etc. can be listed, which can be formed by sputtering, evaporation, coating, etc. The light reflectivity of the anti-reflection film is preferably 5% or less, 4% or less, and particularly preferably 3% or less at a wavelength of 380 to 780 nm.
[0063] As a fine concave-convex structure layer, a moth-eye structure composed of a size below the wavelength of visible light can be cited. As a method for producing a fine concave-convex structure layer, nanoimprinting and photolithography can be cited. Alternatively, the surface of the wavelength conversion component can be roughened by sandblasting, etching, grinding, etc. to form a fine concave-convex structure layer. The surface roughness Ra of the concave-convex structure layer is preferably 0.001-0.3μm, 0.003-0.2μm, and particularly preferably 0.005-0.15μm. If the surface roughness Ra is too small, it is difficult to obtain the desired anti-reflection effect. On the other hand, if the surface roughness Ra is too large, the light scattering becomes larger and the luminous intensity is easily reduced.
[0064] Figure 1 An example of an embodiment of the light emitting device of the present invention is shown. Figure 1 As shown, the light emitting device 1 includes a wavelength conversion component 2 and a light source 3. The light source 3 irradiates the wavelength conversion component 2 with an excitation light L1. The excitation light L1 incident on the wavelength conversion component 2 is converted into fluorescence L2 of another wavelength and emitted from the opposite side of the light source 3. At this time, the composite light of the excitation light L1 and the fluorescence L2 that are transmitted without being wavelength converted can also be emitted.
[0065] Example
[0066] Hereinafter, the present invention will be described in detail based on examples, but the present invention is not limited to these examples.
[0067] (1) Preparation of glass powder
[0068] Tables 1 to 3 show the glass powders (samples 1 to 39) used in Examples and the glass powders (samples 40 and 41) used in Comparative Examples.
[0069] [Table 1]
[0070]
[0071] [Table 2]
[0072]
[0073] [Table 3]
[0074]
[0075] [Table 4]
[0076]
[0077] [Table 5]
[0078]
[0079] The raw materials were prepared to obtain the glass compositions shown in Tables 1 to 5, and the raw materials were melted at 1200 to 1700°C for 1 to 2 hours in a platinum crucible for vitrification. The molten glass was poured between a pair of cooling rollers to form a film. The obtained film-shaped glass molded body was crushed with a ball mill and classified to obtain an average particle size D 50 The glass powder was 2.5 μm in diameter. The thermal expansion coefficient, density, strain point, annealing point, softening point and weather resistance of the obtained glass powder were measured by the following methods.
[0080] The thermal expansion coefficient was measured using a dilatometer at a value in the range of 30 to 380°C.
[0081] The density was measured using the Archimedean method.
[0082] The strain point, annealing point and softening point are measured using the fiber elongation method with a viscosity of 10 14.5 dPa·s, 10 13.0 dPa·s and 10 7.6 dPa·s temperature.
[0083] Weather resistance is evaluated as follows. The glass powder is press-formed with a mold to produce a cylindrical preform with a diameter of 1 cm, and fired at the firing temperature described in Tables 1 to 5 to obtain a cylindrical sintered body sample. Using a HAST tester PC-242HSR2 manufactured by Hirayama Manufacturing Co., Ltd., the sample is kept at 121°C, 95% RH, and 2 atmospheres for 300 hours, and the surface is observed to evaluate the weather resistance. Specifically, an optical microscope is used for observation (×500), and samples with no change in the surface of the sample before and after the test are evaluated as "○", and samples with precipitated glass components on the surface of the sample or loss of gloss are evaluated as "×".
[0084] (2) Fabrication of wavelength conversion components
[0085] Tables 6 to 14 show examples of the present invention (samples A-1 to A-39, B-1 to B-39) and comparative examples (A-40, A-41, B-40, B-41).
[0086] [Table 6]
[0087]
[0088] [Table 7]
[0089]
[0090] [Table 8]
[0091]
[0092] [Table 9]
[0093]
[0094] [Table 10]
[0095]
[0096] [Table 11]
[0097]
[0098] [Table 12]
[0099]
[0100] [Table 13]
[0101]
[0102] [Table 14]
[0103]
[0104] The inorganic phosphor powders shown in Tables 6 to 14 are mixed in the glass powder samples described in Tables 1 to 5 at a predetermined mass ratio to obtain a mixed powder. The mixed powder is press-formed with a mold to produce a cylindrical preform with a diameter of 1 cm. After the preform is fired, the obtained sintered body is processed to obtain a wavelength conversion component with a square size of 1.2 mm and a thickness of 0.2 mm. In addition, the firing temperature is the firing temperature described in Tables 1 to 5 according to the glass powder used.
[0105] The wavelength conversion component is placed on an LED chip with a light emission wavelength of 445nm and powered at 650mA, and irradiated with light continuously for 100 hours. Regarding the wavelength conversion component before and after light irradiation, a general-purpose light emission spectrum measuring device is used to measure the energy distribution spectrum of the light emitted from the upper surface of the wavelength conversion component in an integrating sphere. The total light beam value is calculated by multiplying the obtained light emission spectrum by the standard relative visibility. The rate of change of the total light beam value is expressed by the value (%) obtained by dividing the total light beam value after light irradiation by the total light beam value before light irradiation and multiplying by 100. The results are shown in Tables 6 to 14.
[0106] It can be seen from Tables 6 to 14 that when YAG is used as the inorganic phosphor, the wavelength conversion components of Examples A-1 to A-39 maintain a total beam value of more than 99.5% of that before light irradiation even after 100 hours of light irradiation. In contrast, the total beam value of the wavelength conversion components of Comparative Examples A-40 and A-41 after 100 hours of light irradiation is reduced to less than 98% of that before light irradiation.
[0107] In addition, when α-SiAlON is used as the inorganic phosphor, the wavelength conversion components of Examples B-1 to B-39 maintain a total beam value of more than 99% of that before light irradiation even after 100 hours of light irradiation. In contrast, the total beam value of the wavelength conversion components of Comparative Examples B-40 and B-41 after 100 hours of light irradiation is reduced to less than 94% of that before light irradiation.
[0108] Industrial Applicability
[0109] The wavelength conversion member of the present invention is suitable as a component of general lighting such as white LEDs or special lighting (for example, projector light sources, vehicle-mounted lighting such as vehicle headlights), and the like.
[0110] Explanation of symbols
[0111] 1 Light-emitting devices
[0112] 2 Wavelength conversion components
[0113] 3 Light Source
Claims
1. A wavelength conversion component, characterized in that: It is a wavelength conversion component in which inorganic phosphors are dispersed in a glass matrix. The glass matrix contains, in mole percent, 30-85% SiO2, 0-20% B2O3, 0-25% Al2O3, 0-3% Li2O, 0-3% Na2O, 0-3% K2O, 0-3% Li2O+Na2O+K2O, 0-35% MgO, 0-35% CaO, 0-35% SrO, 0.1-35% BaO, 0.1-45% MgO+CaO+SrO+BaO, and 0-4% ZnO. The softening point of the glass matrix is 829-1100°C. The inorganic phosphor is at least one selected from oxide phosphors, nitride phosphors, oxynitride phosphors, chloride phosphors, acyl chloride phosphors, halide phosphors, aluminate phosphors and halophosphate phosphors.
2. The wavelength conversion component according to claim 1, characterized in that: The glass matrix contains ZnO in an amount of 0 to less than 1.8% by mol%.
3. The wavelength conversion component according to claim 1 or 2, characterized in that: The glass matrix contains 61.5-85% SiO2 in mol%.
4. The wavelength conversion component according to claim 1 or 2, characterized in that: The glass matrix contains 0 to 9.5% of CaO in terms of mol%.
5. The wavelength conversion component according to claim 1 or 2, characterized in that: The inorganic phosphor is contained in an amount of 0.01 to 70% by mass.
6. The wavelength conversion component according to claim 1 or 2, characterized in that: Formed from powder sintered body.
7. A light emitting device, characterized in that: include: The wavelength conversion member according to any one of claims 1 to 6, and a light source for irradiating the wavelength conversion member with excitation light.
8. A vehicle-mounted lighting device, characterized in that: The light emitting device according to claim 7 is used.
9. The vehicle-mounted lighting device according to claim 8, characterized in that: Used as a headlamp.
Citation Information
Patent Citations
JP1973095541A
Light-emitting diode
JP2000208815A
Emission color converting member
JP2003258308A
Luminescent color-shifting material and luminescent color-shifting member
JP2007302858A
Wavelength conversion member and semiconductor light-emitting element device having and using the wavelength conversion member
JP2011222751A